Усилитель с компенсацией постоянной составляющей выходного напряжения: полезная модель - Ким В. Л. Валерий Львович; Андреев С. А. Семён Алексеевич; Мальчуков А. Н. Андрей Николаевич; Мыцко Е. А. Евгений Алексеевич
опубл. 10.10.16